Jute-Gate: A Case Study on the Development of a Subject Gateway - Sanyal, Surojit; Bandyopadhyay, Ratna; Panigrahi, Pijushkanti (Journal of Information and Knowledge, 2017)
Documents on Jute have proliferated considerably along with the growth of the Jute Industry. The aim of this study is to develop a comprehensive single-window knowledge dissemination tool on Jute. Survey of subject gateways and Jute websites has been conducted to ascertain the need for the same. Development of a subject gateway on Jute information (i.e. Jute-Gate) is an obvious choice as there is no subject gateway on Jute, although different subject gateways have been developed across the world for disseminating qualitative information to information seekers on other subjects. A prototype Jute-Gate has been designed based on the feedback from a field survey of Jute Mills and other stakeholders using a free open-source Content Management Software (CMS) (i.e. Drupal).